Unraveling Ibn Sabʿīn’s Thought: A Study of Verified and Unverified Texts - Na'amneh, Mahmoud; Assadi, Jamal; Sindawi, Khaled (Journal of Posthumanism, 2025)
Abd al-Ḥaqq Ibn Sabʿīn al-Andalusī (614–669 AH / 1217–1269 CE), also known as "Abū ʿAlī al-Ḥasan ibn ʿAlī ibn Muḥammad ibn Sabʿīn," was a central figure in medieval Islamic Ṣūfism. Born in the city of Murcia in al-Andalus, Ibn Sabʿīn was renowned for his philosophical-mystical approach, which sparked significant controversy both during his lifetime and in subsequent eras. His thought diverged from mainstream Ṣūfī traditions, leaving a lasting impact on Islamic philosophical and mystical discourse. While his intellectual contributions remain highly influential, his nonconformist ideas and bold reinterpretations of theological principles positioned him as a figure of both admiration and contention. This study explores Ibn Sabʿīn’s verified and unverified manuscripts, shedding light on his unique intellectual contributions, his use of argumentation and intuition, and the authority of textual interpretations in his works. It examines his engagement with Greek philosophy, his critiques of religious orthodoxy, and his doctrine of waḥdat al-muṭlaqah (absolute unity), which went beyond the concept of waḥdat al-wujūd (unity of being). Additionally, the research investigates lost manuscripts attributed to him, assessing their content, authenticity, and historical significance. The study also explores the role of his "Sabʿīnian Additions" in shaping later Ṣūfī thought, particularly in the Maghreb and Ottoman intellectual traditions. By analyzing his philosophical and theological positions, linguistic complexities, and historical reception, this research contributes to a deeper understanding of his influence on Ṣūfī metaphysics and epistemology. Through a comparative framework, the study situates Ibn Sabʿīn within the broader intellectual landscape of medieval Islam, positioning him as both a radical innovator and a controversial mystic.